PROMOTION OF CLEAN COAL TECHNOLOGIES FOR MEETING ENERGY DEMANDS IN A SUSTAINABLE MANNER (Journal of Mechanical Engineering, 2013)
The global energy requirement has grown at a phenomenon rate and the demand of coal willcontinue to remain as the prime energy source in foreseeable future . Economic development and povertyalleviation depend on securing affordable energy sources and coal mining industry offers a bright future for theenergy security in the Asia Pacific Region, However, direct use of coal leads to environmental pollution. Theemission of CO2' the principal green house gases (GHG), is strongly related to the use of fossil fuel, especiallycoal, for energy production. A long term projection for the Indian energy sector up to the year 2031-32 showthat CO2 emission from India is likely to increase much faster to 3.5 times the present value. Estimated globaltemperature increase varying from 2 to 3.5°C and a sea level rise of 65 cm by the year 2100. As coal will bereaming as the prime energy source this paper emphasizes the need to develop clean coal technologies wherecoal can be refined in coal refineries to obtain different fractionated products having different quality gradeclass (QGC) of fuels. It also highlights the need to develop further clean coal technologies like integratedgasification combined cycle (IGCC) through hydrogen generation for zero emission. The use of ultra clean coalin gas turbines directly will enhance the efficiency of power generation to 52-55% from the existing efficiency ofpulverized coal power generation of 33 - 38%. This paper discusses the role of Mechanical Engineers for thepromotion of Clean Coal Technology (CCT) in fulfilling energy demand in a sustainable manner. Brute forcehigh pressure coal conversion processes will have to be replaced by the convenient and cost effective lowatmospheric pressure processes through further research and development work. The methodology as discussedmay have formed a guideline to develop clean coal technologies in industrial scale in various countries.DOI: http://dx.doi.org/10.3329/jme.v42i1.15931